Service Science and Knowledge Innovation: 15th IFIP WG 8.1 International Conference on Informatics and Semiotics in Organisations, ICISO 2014, Shanghai, China, May 23-24, 2014, Proceedings - Liu, Kecheng; Gulliver, Stephen Richard; Li, Weizi; Yu, Changrui (Service Science and Knowledge Innovation 15th IFIP WG 8.1 International Conference on Informatics and Semiotics in Organisations, ICISO 2014, Shanghai, China, May 23-24, 2014. Proceedings, 2014)
This book constitutes the refereed proceedings of the 15th IFIP WG 8.1 International Conference on Informatics and Semiotics in Organisations, ICISO 2014, held in Shanghai, China, in May 2014. The 39 revised papers presented at the main conference were carefully reviewed and selected from 88 submissions. Additionally, 10 papers were selected for presentation at two workshops held in the framework of ICISO 2014. The papers have been organized in the following topical sections: organizational semiotics: theory and concepts; organizational semiotics and applications; finance and service science; enterprise architecture; modelling and simulation and decision making and knowledge management. The last two sections contain papers from the Workshop on e-Health, the New Frontier of Service Science Innovation and the International Workshop on Information Engineering and Management.